Evaluation of the effectiveness of risperidone in the treatment of breath holding spells in children - Zamani, Gholamreza; Abdi, Alireza; Heydari, Morteza; Ashrafi, Mahmoud Reza; Tavasoli, Ali Reza (Iranian Journal of Child Neurology, 2023)
Objectives Breath holding spells (BHS) are a type of syncope in children that is commonly seen in the first years of life. Although these attacks do not cause serious damage to the child's brain, in severe or repeated cases, they expose the brain to hypoxia and cause a lot of stress in parents. In these cases, the clinician should consider therapy. The purpose of this study is to investigate the effectiveness of Risperidone in the treatment of BHS in children visiting the neurology clinic of the Children's Medical Center Hospital. Materials & Methods In this randomized clinical trial, the statistical population included patients with the history of Breath Holding spells grades 2 to 3 (after ruling out of seizure disorders) over one year old, visiting the neurology clinic of Tehran Children's Medical Center in 2019. The subjects were randomly selected from patients visiting the clinic using a table of random numbers from the admit ion list. After providing the necessary explanations and obtaining informed consent from their parents, they were treated with low-dose Risperidone (maximum 1 mg) for three months. The patients were observed for three months in terms of frequency and severity of spells monthly. Results In this study, the median (25th and 75th percentile) age of subjects was 2.3 (2.0-2.6) years. Both the number and severity of seizures in the subjects had a statistically significant decrease in the period after treatment with Risperidone (P<0.001). The studied boys and girls experienced statistically significant decrease in terms of both the frequency of spells (P-value of 0.002 and 0.039) and intensity of seizures (P=0.016) and P=0.008), respectively after treatment with Risperidone. Also, in the studied children under 2 years old and over 2 years old, both the frequency (P=0.021 and P=0.004) and intensity of spells (P=0.008) 0.016 for subjects under and over 2 years, respectively) had a statistically significant decrease after treatment with risperidone compared to pretreatment. Conclusion According to the results of this study, it seems that both the frequency and the intensity of spells in children (regardless of gender and age group), experienced a statistically significant decrease after treatment with Risperidone. We suggest conducting a more comprehensive study considering a larger sample size in order to estimate this issue more correctly.